Some Problems of Pedophilia Crimes Delimitation - Yu. S. Pestereva; I. A. Kuznetsova (Сибирское юридическое обозрение, 2013)
The article deals with the analysis of the changes contributed by the lawmaker to the RF Criminal Code. Here are distinguished contradictory and collision norms, the problems of their qualification. Some scientific points of view are quoted. The authors offer the ways of solving problematic issues connected with strengthening of the responsibility for crimes of sexual character committed in relation to non-adults.